PERAN ORANG TUA DALAM PEMBELAJARAN AKIDAH AKHLAK BERBASIS DARING DI MTs ROUDHOTUL UQUL PAKISAJI MALANG - Anisa Faizatul Azatama; Anwar Sa’dullah; Devi Wahyu Ertanti (VICRATINA, 2021)
Parents in this sense are people who already have families who have children and are the responsibility and are in their care. The parents referred to by the researcher are parents who have cared for and educated children in the family and become responsibilities both in the formal and non-formal fields. The research method used is a qualitative method with the type of case study research. Data collection in this study used observations, interviews, and documentation to school principals, teachers of morals, parents, and students. as for the data analysis technique using data reduction, data presentation, and drawing conclusions. The results of the study indicate that the role of parents in the formation of children's morals during online learning is very good and in accordance with existing ones. Where parents always fulfill the obligations of a child in terms of education, knowledge, supervision, protection, and partners. Children's morals in online learning are declining, where children's morals are not the same as usual and efforts are made so that children can continue to maintain good and correct morals according to what is available.